Strategic Resilience in Public Service Delivery: Lessons from a Post-Pandemic Adaptive Governance Model - Harjono Harjono; Yitno Puguh Martomo; Dion Candra Wardana; Bambang Supriadi (Relasi : Jurnal Ekonomi, 2026)
The COVID-19 pandemic catalyzed unprecedented changes to the governance ecosystem of public service delivery, redirecting scholarly and policy interest from operational continuity to strategic resilience. By integrating recent literature from 2020 to 2026, it constructs a framework of strategic resilience in public service provision. This study follows a Systematic Literature Review (SLR) approach according to PRISMA 2020 guidelines combining bibliometrics visualization and analyzes 54 peer-reviewed articles indexed in Scopus and Web of Science. The results show a decisive shift in the conceptualization of strategic resilience from crisis-response resilience to transformation-oriented strategic resilience. Five intertwined determinants coalesce into a number of foundational dimensions: adaptability, digital maturity, collaborative governance, institutional flexibility, and leadership agility. These findings demonstrate that strategic resilience is not only about bouncing back from disruption but also the reconfiguration of institutional arrangements, interdependence of digital infrastructures, and sustainable public value in epistemic uncertainty. By grafting dynamic capability theory onto adaptive governance and public value theory, the study presents a cross-cutting model of resilience as not just an ad hoc crisis device but instead a long tail governance paradigm. The suggested framework advances theoretical knowledge in the field while providing practical guidance for policymakers striving to embed resilience within public sector reform agendas. Longitudinal quantitative methods will be an excellent opportunity to continue testing out the robustness of the model across governance contexts.